Caracterización de los hábitos alimentarios y estilos de vida de los niños, de la institución obra misionera Jesús y María, Jardín Sol-Solecito, localidad de Suba, Bogotá D.C. - Andrea Cuervo-Lozada; Gladys Liévano- De Lombo; Martha Leclerecq-Barriga; Martha Liévano-Fiesco; Gloria García-Londoño (Universitas Scientiarum)
Characterization of food habits and lifestyles of children attending the Sol Solecito Kindergarden in Suba, Bogotá, D.C. Thisstudy was aimed to characterize the food habits and lifestyles of the children of the Sol Solecito Kindergarden in Bogotá, D.C., using theLund and Burk model as the conceptual framework for the analysis of conduct of children in relation to food. The study was descriptive andcross sectional. The sample consisted of 54 children, selected by a proportional random-stratified sampling. Children’s nutritional statusaccording to the Weight/Age Index showed normality for 68.8% of them; when classified by Weight/Age Index, 53.8% showed normality,for the Weight/Stature Index 52.1% showed normality but 35.8% of the children revealed overweight, a result not reported in previousstudies. The percentage of families having both parents was 81% and parents ages ranged from 15 to 54 years old. Foods preferred bychildren were: milk, yogurt, rice, pasta, chicken, candy, fruits, and fruit juices. Rejected foods were lettuce and cassava. The most frequenthealth problem was influenza. 40.7% of the children practice a sport but not on a routinely basis. On average, 50% of the children watchtelevision 2-3 hours daily. Parents and teachers expressed their interest in receiving qualified training on nutrition since they consider itimportant for the child’s growth and development. Based on the results of our study, we designed a training program aimed to improve thefood habits and therefore the nutritional status of the children.